2017
DOI: 10.1021/acs.jafc.7b03239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Associated with the Rearing Practices, Carcass Characteristics, and Beef Quality: An Integrative Approach

Abstract: Data from birth to slaughter of cull cows allowed using a PCA-based approach coupled with the iterative K-means algorithm the identification of three rearing practices classes. The classes were different in their carcass characteristics. Old cows raised mainly on pasture have better carcass characteristics, while having an equivalent tenderness, juiciness, flavor, intramuscular fat content, and pHu to those fattened with hay or haylage. The Longissimus thoracis muscle of the cows raised on pasture (with high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 48 publications
9
99
0
Order By: Relevance
“…Long fattening duration is not suitable because it leads to tough meat. This confirms our hypothesis dealing with the importance of the determination of the optimum thresholds of the factors governing the fattening period to achieve the best income and sustainability in cattle production . Recently, we pointed out this importance, and proposed to take in account the fattening duration in relation with further traits such as fat tissue and muscle percentages of young bulls .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Long fattening duration is not suitable because it leads to tough meat. This confirms our hypothesis dealing with the importance of the determination of the optimum thresholds of the factors governing the fattening period to achieve the best income and sustainability in cattle production . Recently, we pointed out this importance, and proposed to take in account the fattening duration in relation with further traits such as fat tissue and muscle percentages of young bulls .…”
Section: Discussionsupporting
confidence: 84%
“…This confirms our hypothesis dealing with the importance of the determination of the optimum thresholds of the factors governing the fattening period to achieve the best income and sustainability in cattle production . Recently, we pointed out this importance, and proposed to take in account the fattening duration in relation with further traits such as fat tissue and muscle percentages of young bulls . In cattle, several studies reported significant morphological changes that take place in the carcass, and hence on muscle, during the fattening period, as well as how these are to some extent confounded with age .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the variables of interest to investigate the trend of differences among M and AT was illustrated by a principal component analysis (PCA), performed on raw data, by considering all the factors together including tenderness as a supplementary variable. Two factors with eigenvalues > 1.0 were considered in this PCA on the basis of the scree plot and evaluation of the factor loading matrix after orthogonal rotation following the procedure described by Gagaoua et al . An eigenvalue represents the amount of variance that is captured by a given component.…”
Section: Methodsmentioning
confidence: 99%
“…age at slaughter, carcass weight, CS and FS of the carcasses were centered and scaled by computing z ‐scores using PROC STANDARD of SAS. After that, principal component analysis (PCA) combined with agglomerative hierarchical cluster analysis (HCA) or k ‐means cluster analyses were undertaken to create animal groups . Two factors with eigenvalues > 1.0 were extracted on the factor loading matrix after orthogonal rotation.…”
Section: Methodsmentioning
confidence: 99%